Numerical Study of N-Heptane Fuelled Hcci Under Different Air Fuel Ratio and Inlet Air Temperature - H., Hanafi; M. M., Noor; M. M., Rahman; K., Kadirgama; D., Ramasamy; C. K., Ihsan; M. K., Kamarulzaman; Y., Selvaraj (2016)
This paper examines on numerical modeling of Homogenous Charge Compression Ignition (HCCI) engine model using n-heptane as base fuel. The parameters used in this study is different air to fuel ratio (AFR) (25, 30, 35, 40, 45, 50) and different air inlet temperature (25°C, 50°C, 75°C, 100°C). Performance and emission characteristics of n-heptane were investigated at constant engine speed of 1000 rpm in a HCCI engine model. The effects of inlet air temperature were also examined. The test results showed that brake power, brake mean effective pressure and brake specific fuel consumption decreased when increased AFR and inlet air temperature. Meanwhile, brake thermal efficiency shows an increase when increase when AFR and temperature of the inlet increased. The test results also showed that NOx, CO and HC emissions decreased with the increase of inlet air temperature for all AFR value. Overall, this numerical model can be used to predict the performance and emission of the HCCI engine.